A case in which a near-infrared ray catheter (NIRC) was effectively applied in laparoscopic sigmoidectomy for a sigmoidovesical fistula. (January 2022) - Okamoto, Atsuko; Ryu, Shunjin; Kitagawa, Takahiro; Marukuchi, Rui; Hara, Keigo; Ito, Ryusuke; Nakabayashi, Yukio
Abstract: A 40-year-old man visited the hospital for a refractory urinary tract infection. A sigmoidovesical fistula resulting from a sigmoidovesical diverticulum was diagnosed, and laparoscopic surgery was performed. To avoid ureteral injury during surgery for highly advanced cancer and inflammatory diseases, a ureteral stent is generally placed before the procedure. However, in this case, surgery was performed using a near-infrared ray catheter (NIRC), which emits fluorescence when irradiated with near-infrared light. By clearly observing the pathway of the ureter via near-infrared light, the integrity of the ureter could be preserved, and sigmoidectomy was safely performed. The visual navigation of the ureter with NIRC was especially useful during surgery for a colovesical fistula with marked surrounding inflammatory changes and a high risk of ureteral damage. Highlights: To avoid ureteral injury during surgery, surgery was performed using a near-infrared ray catheter (NIRC) NIRC could be observed clearly the pathway of the ureter via near-infrared light. The visual navigation of the ureter with NIRC was especially useful during surgery for a colovesical fistula.